2020
DOI: 10.1177/1475921720971551
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue damage diagnosis and prognosis of an aeronautical structure based on surrogate modelling and particle filter

Abstract: A key issue affecting the performances of every human-conceived engineering system is its degradation, fatigue crack growth being one of the major structural deterioration phenomena. Fatigue crack growth is usually modelled as a stochastic process: uncertainty sources lie both in the item and in the physical degradation process variability. Fatigue crack growth deserves close attention, especially considering that condition-based maintenance methodologies are recently experiencing a major drive to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…NN models are widely used as prognostics and health management tools to obtain a clear picture of the health state of the material (diagnosis) and an estimation of the remaining fatigue life (prognosis) 169 . This section is organized by fatigue diagnosis followed by fatigue prognosis.…”
Section: Review Of Nn Applications In Fatiguementioning
confidence: 99%
“…NN models are widely used as prognostics and health management tools to obtain a clear picture of the health state of the material (diagnosis) and an estimation of the remaining fatigue life (prognosis) 169 . This section is organized by fatigue diagnosis followed by fatigue prognosis.…”
Section: Review Of Nn Applications In Fatiguementioning
confidence: 99%
“…3,44 In implementing the PF, at each time step, N p process noise samples will be sampled from the distributions in Table 2 and assigned to the N p particles. The noise distributions in this study are determined from Corbetta et al and Cristiani et al, 3,9,10 while the means and STDs are selected based on a trial-and-error procedure.…”
Section: Pf Parametersmentioning
confidence: 99%
“…From the perspective of how the prognostic models are formulated, they can be classified into physics-based, [1][2][3] data-driven, [4][5][6] and hybrid methods. [7][8][9][10][11] Physics-based methods utilize specific mechanistic knowledge and theories to formulate pure physics-based models, which describe the structural degradation phenomena and the links between the damage states and the SHM measurements. Data-driven methods, resorting to data-driven modeling techniques such as neural networks 4,6 and Markov chains, 5 attempt to use a large amount of data to build the relationship between the internal degradation behavior and the external observations.…”
mentioning
confidence: 99%
“…All the PF parameters used in this study are reported in Table 3. The strategies about the distributions of initial intervals for C and m and the process noise ω are determined from [3,11,12].…”
Section: Particle Filter Parametersmentioning
confidence: 99%
“…In the last decades, a great variety of damage prognosis techniques have been developed in SHM depending on the availability of physics knowledge and data. From the perspective of how the prognosis models are formulated, they can be distinguished into physics-based [1][2][3], data-driven [4][5][6][7][8] and hybrid methods [9][10][11][12][13]. Physics-based methods utilize specific mechanistic knowledge and theories to formulate a pure physics-based model, which describes the structural degradation phenomena as well as the links between the damage states and the SHM measurements.…”
Section: Introductionmentioning
confidence: 99%